2020
DOI: 10.3390/ijerph18010072
|View full text |Cite
|
Sign up to set email alerts
|

Living in a Larger Body: Do Exercise Motives Influence Associations between Body Image and Exercise Avoidance Motivation?

Abstract: The study explored reasons for exercise as possible mediators of the relationship between body appreciation and exercise avoidance motivation and between body surveillance and exercise avoidance motivation. Using a cross-sectional design, 131 women with a body mass index (BMI) of 25 or higher completed measures of body surveillance, body appreciation, reasons for exercise, and exercise avoidance motivation. Mediation analyses indicated that appearance-oriented reasons for exercise partially mediated the body s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…': (a) I feel like other people are constantly judging me, (b) I'm uncomfortable with the idea of going to the gym where there are a lot of mirrors, (c) I don't go to the gym because there are a lot of slim people there. In the current research, Cronbach's α = 0.83, which is in line with reliability reports by [11], who reported a reliability of 0.79 for the full scale, and [41], who reported an α of 0.88.…”
Section: Methodssupporting
confidence: 91%
“…': (a) I feel like other people are constantly judging me, (b) I'm uncomfortable with the idea of going to the gym where there are a lot of mirrors, (c) I don't go to the gym because there are a lot of slim people there. In the current research, Cronbach's α = 0.83, which is in line with reliability reports by [11], who reported a reliability of 0.79 for the full scale, and [41], who reported an α of 0.88.…”
Section: Methodssupporting
confidence: 91%
“…Several theories have been used for the study and understanding of behavioral change, seeking to help this change in individuals in highly varied contexts. According to Michie et al [6], in a study where 83 theories related to behavioral change were presented, more than 30 of these theoretical models addressed motivation. However, self-determination theory (SDT) [7,8] has been the most used supporting theoretical framework to explain people's cognitive, behavioral, and emotional patterns in physical exercise [4,9].…”
Section: Self-determination Theorymentioning
confidence: 99%
“…A recent study has shown that individuals will drop out in the first stages of practice [5]. In line with motivational theories, previous research has not provided a comprehensive examination of alternative cognitive factors when analyzing the commitment to exercise among individuals engaged in gym or fitness activities, such as body image (BI) and eating behavior [6]. Social networks influence the creation of stereotypes regarding the idea of an ideal body, usually with a distorted view of the BI.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, exercise environments are not usually welcoming toward women whose bodies deviate from size‐normative standards of attractiveness, beauty, and the thin ideal (Flint & Reale, 2018; Schvey et al, 2017). Vartanian and Shaprow (2008) found that women with larger bodies avoid exercise due to the stigma toward obese individuals (Bombak, 2015; Greenleaf & Rodriguez, 2020; Meadows & Bombak, 2018). The globally increasing obesity rate reflects that the majority of the population has fallen below the recommended amounts of physical activity required for good health (Hill & Wyatt, 2005).…”
Section: Hypotheses Developmentmentioning
confidence: 99%